Venus Flytrap HKT1-Type Channel Provides for Prey Sodium Uptake into Carnivorous Plant Without Conflicting with Electrical Excitability - Böhm, J.; Scherzer, S.; Shabala, S.; Krol, E.; Neher, E.; Mueller, T.D.; Hedrich, R. (Molecular plant, 2016)
The animal diet of the carnivorous Venus flytrap, Dionaea muscipula, contains a sodium load that enters the capture organ via an HKT1-type sodium channel, expressed in special epithelia cells on the inner trap lobe surface. DmHKT1 expression and sodium uptake activity is induced upon prey contact. Here, we analyzed the HKT1 properties required for prey sodium osmolyte management of carnivorous Dionaea. Analyses were based on homology modeling, generation of model-derived point mutants, and their functional testing in Xenopus oocytes. We showed that the wild-type HKT1 and its Na^＋- and K^＋-permeable mutants function as ion channels rather than K^＋ transporters driven by proton or sodium gradients. These structural and biophysical features of a high-capacity, Na^＋-selective ion channel enable Dionaea glands to manage prey-derived sodium loads without confounding the action potential-based information management of the flytrap.